2022
DOI: 10.3390/ijerph19063353
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Factors Associated with Sport Participation among Adolescent Females

Abstract: Sport participation provides a direct means to attain health-enhancing physical activity; however, sport participation declines during adolescence, and over 85% of adolescent females fail to meet the recommended 60 min of moderate-vigorous physical activity daily. Given the importance of overcoming barriers to sport and increasing equity in women’s sports, the purpose of this systematic review was to identify factors associated with sport participation among adolescent girls and operationalize those factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…In the process of individual development, boys were more active than girls, and their level of PA was higher than girls. Hopkins et al (2022) found that the self-concept related to physical exercise was closely related to the physical exercise of female adolescents through a comprehensive analysis. The study emphasized the need for improvement in macro and micro aspects to improve adolescents’ PA and promote fairness ( Ricardo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the process of individual development, boys were more active than girls, and their level of PA was higher than girls. Hopkins et al (2022) found that the self-concept related to physical exercise was closely related to the physical exercise of female adolescents through a comprehensive analysis. The study emphasized the need for improvement in macro and micro aspects to improve adolescents’ PA and promote fairness ( Ricardo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, students with a higher level of regular PA practice registered more intrinsic motivation and identified regulation towards PE and lower motivation in those who do not practice DFA. Other personal factors, such as sport self-concept, physical self-concept or perceived competence, are also key predictors of future PA [ 51 , 52 , 53 ]. It is also observed how factors related to self-perception and those that were most frequently associated with enjoyment and potential health benefits become motivational factors that influence self-determination to perform PA among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, boys show greater ego-orientation in PA practice [ 56 , 57 , 58 ]; in turn, females are more inclined to less sporty activities, whereas males tend to be more predisposed to competition [ 57 , 59 , 60 ]. However, in the systematic investigation by Hopkins et al [ 53 ], the importance of adolescent girls’ attitudes or behavioral beliefs is highlighted when considering their motivation to participate in or continue with sports over time.…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in this review describe complex social and environmental conditions that impact development, implementation, and evaluation of sport-based interventions, and influence participation among athletes and mentors/coaches; however, outcomes were measured at the individual and social levels only. A recent systematic review of factors associated with sport participation among adolescent females identified relevant factors across biological, personal, social, socioeconomic, and environmental or resource levels [ 45 ], indicating the need for additional multilevel research approaches to provide a more complete picture of the field. Furthermore, application of theoretical models addressing broad levels of influence, such as policy, and incorporating targeted strategies across the life course, such as the Physical Activity and Sport Participation Framework which frames sport within the context of policies and approaches to achieve population-wide recommended levels of PA, can advance the field by linking evidence to actionable outcomes relevant across programmatic settings at local and national levels [ 46 ].…”
Section: Discussionmentioning
confidence: 99%